Direct effect of urea and vermicompost on growth and seed yield of bottle gourd and their residual effect on succeeding carrot - Bairwa, L.N.; Khandelwal, S.K. (Annals of Agricultural Research, 2016)
A field experiment was conducted to ascertain the influence of urea and vermicompost on growth and seed yield of bottle gourd and their residual effect on succeeding carrot crop at Agriculture Research Station, Durgapura, Jaipur during 2004-05 and 2005-06. The recommended dose of nitrogen (RDN) was supplied through urea and vermicompost in different combinations. It was found that integrated use of nitrogen significantly influenced the growth, yield attributing characters, yield and nutrient content in seed. 50% RDN through urea and 50% RDN through vermicompost was found to be the most significant not vine length, number of primary branches, fruit length and girth, number of fruits (2.99) per vine, number of seeds (464.3) per fruit and seed yield (1012.5 kg/ ha). After harvest of bottlegourd seed crop, carrot was sown on layout with recommended package and practices. It revealed that 100% RDN through vermicompost recorded maximum root length, root width and yield of succeeding carrot crop.